The Effectiveness of Halal Certification Regulations for MSME Operators in Consumer Protection Efforts - Marlina, Tina; Umar, Jaenudin; Budiyanti, Setia; Aufiya, Zelfi Ghaffar; Ika Putri, Dessy; Wahyudin, Hafidz (Ann Publisher, 2025)
Background, The requirement for halal certificates for Micro, Small, and Medium Enterprises (MSMEs) is articulated in the Halal Product Guarantee Law, the Consumer Protection Law, the Job Creation Law, and Government Regulations concerning the Implementation of the Halal Product Guarantee Sector. This is facilitated by the provision of a complimentary halal certificate policy from BPJPH, aimed at enhancing consumer protection through MSME products, ensuring their health, comfort, and safety are assured. Aim, This study seeks to assess the efficacy of compulsory halal certification regulations for MSMEs in the Pekiringan and Sunyaragi subdistricts. Methods, The employed research approach is empirical juridical, focusing on the existing laws within society, particularly with the enforcement of mandatory halal certificate restrictions in the two sub-districts. Results, The MSME actors sampled in this study refrain from acquiring halal certificates due to apprehensions regarding the associated high expenses and also believe that the process of issuing halal certificates will incur a significant tax burden after the halal certificate is issued. Conclusions, The research findings on MSMEs in Pekiringan and Sunyaragi Subdistricts indicate that the enforcement of mandatory halal certification regulations is ineffective, as numerous MSME operators remain uncertified due to concerns over high costs and subsequent taxation following the issuance of the halal certificate. Implication, The effectiveness of halal certification regulations for MSME operators in consumer protection efforts is lacking, considering they are apprehensive about the costs involved during and after halal certification.